Injectable Biopolymer-hydroxyapatite Hydrogels: Obtaining and their Characterization - L.B. Sukhodub; G.O. Yanovska; V.M. Kuznetsov; O.O. Martynyuk; L.F. Sukhodub (Журнал нано- та електронної фізики)
Hydrogels based on hydroxyapatite (HA) and Chitosan (CS) with addition of sodium alginate (Alg) were synthesized by in situ precipitation method. Structure, morphology, chemical and phase composition of the HA/CS and HA/CS/Alg hydrogels were characterized by TEM, FTIR and XRD. Hydrogels consist of low crystallinity calcium deficient hydroxyapatite (JCPDS 9 432), the needle-like crystallites have an average size 25 nm. The introduction of Alginate powder into HA/CS hydrogel solution demonstrate the viscosity enhancing of the HA/CS hydrogel due to polyelectrolyte reaction between Alginate and Chitosan macromolecules. Two natural polymers and partially released from hydroxyapatite Ca2+ ions formed a matrix by crosslinking the polymer macromolecules through hydroxyl, amino and carbonyl groups. These processes promote the formation of a more stable structure of HA/CS/Alg hydrogel as compared to HA/CS. The structural integrity and degradation tests have demonstrated that HA/CS/Alg1.0 saved its initial shape in 7 days of shaking in SBF solution, meanwhile for HA/CS, a structural decay was observed. The HA/CS hydrogel had completely lost its volume support after 1 day shaking in SBF. Thus, the ability of HA/CS hydrogel to maintain its shape with implantation into bone tissue defect may be enhanced with alginate addition, but alginate content more than 1 w/w % reduces the hydrogel plasticity, increases the swelling and accelerates the shape decay.